การพัฒนาแนวปฏิบัติในการป้องกันโรคหลอดเลือดสมองในกลุ่มผู้ที่เป็นโรคความดันโลหิตสูง สำหรับอาสาสมัครสาธารณสุขประจำหมู่บ้าน โรงพยาบาลส่งเสริมสุขภาพตำบลตาลชุม อำเภอเวียงสา จังหวัดน่าน - วิลาภา ยศมาดี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Stroke prevention in persons with hypertension is important in reducing incidents that cause strokes. This study aimed to develop stroke prevention practice guidelines in persons with hypertension for village health volunteers in Tan Chum Tambon, Wiang Sa District, Nan Province. The following developmental procedures were conducted according to the guidelines from The Thailand Centre for Evidence-Based Nursing, Midwifery & Health Science, Faculty of Nursing, Chiang Mai University. These guidelines were used to: 1) determine problems; 2) identify outcomes; 3) search for evidences; 4) appraise evidence; and 5) develop stroke prevention practice guidelines for village health volunteers. This process was conducted between July 2013 and July 2014. Guidelines were developed by 10 developmental team members and was tried out by 5 village health volunteers who cared for persons with hypertension in Tan Chum Tambon, for 2 weeks. Tools used in this study consisted of: 1) general questionnaires for practice guidelines developmental team members and practice guidelines users; and 2) user evaluation questionnaires regarding the quality of the practice guidelines. Data were analyzed using frequency distribution and descriptive statistics. The practice guidelines as the result of this study consisted of 5 sections: 1) stroke risk assessment; 2) hypertension and stroke health education; 3) stroke prevention activities; 4) patient referral when abnormality was found; and 5) outcome evaluation. The users highly agreed that the practice guidelines were efficient, feasible and practical. Therefore, the practice guidelines should be implemented and disseminated.